JOB ANALYSIS DAN EFISIENSI KERJA LEMBAGA PENDIDIKAN - Hasanah, Suci Uswatun; Idris, Eka Putra; Saepudin Mashuri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2021)
This paper deals with job analysis and work efficiency in educational institutions. Job analysis seeks to provide information to workers about job activities, job standards, job context, personnel requirements, human behavior, tools used and job procedures for each employee. Through qualitative methods and literature review design, this paper aims to reveal urgent job analysis and redesign in positioning human resources according to their field of knowledge and competence. Implementation of job analysis and redesign based on changes in performance that can increase the productivity of employees of educational institutions. Through job analysis, leaders obtain information about job descriptions and job specifications needed, determine standards, success criteria and evaluate work results that have been achieved. In addition, leaders can use it to determine policies and programs to improve employee work efficiency more optimally according to the vision, mission, goals, and profiles of graduates to be achieved by an educational institution.